Structural insights into mechanisms for inhibiting amyloid β42 aggregation by non-catechol-type flavonoids. Issue 2 (15th January 2016) - Hanaki, Mizuho; Murakami, Kazuma; Akagi, Ken-ichi; Irie, Kazuhiro
Graphical abstract: Abstract: The prevention of 42-mer amyloid β-protein (Aβ42) aggregation is promising for the treatment of Alzheimer's disease. We previously described the site-specific inhibitory mechanism for Aβ42 aggregation by a catechol-type flavonoid, (+)-taxifolin, targeting Lys16, 28 after its autoxidation. In contrast, non-catechol-type flavonoids (morin, datiscetin, and kaempferol) inhibited Aβ42 aggregation without targeting Lys16, 28 with almost similar potencies to that of (+)-taxifolin. We herein provided structural insights into their mechanisms for inhibiting Aβ42 aggregation. Physicochemical analyses revealed that their inhibition did not require autoxidation. The 1 H– 15 N SOFAST-HMQC NMR of Aβ42 in the presence of morin and datiscetin revealed the significant perturbation of chemical shifts of His13, 14 and Gln15, which were close to the intermolecular β-sheet region, Gln15-Ala21. His13, 14 also played a role in radical formation at Tyr10, thereby inducing the oxidation of Met35, which has been implicated in Aβ42 aggregation. These results suggest the direct interaction of morin and datiscetin with the Aβ42 monomer. Although only kaempferol was oxidatively-degraded during incubation, its degradation products as well as kaempferol itself suppressed Aβ42 aggregation. However, neither kaempferol nor its decomposed products perturbed the chemical shifts of the Aβ42 monomer. Aggregation experiments using 1, 1, 1, 3, 3, 3-hexafluoro-2-propanol-treated Aβ42 demonstrated that kaempferol and its degradation products inhibited the elongation rather than nucleation phase, implying that they interacted with small aggregates of Aβ42, but not with the monomer. In contrast, morin and datiscetin inhibited both phases. The position and number of hydroxyl groups on the B-ring of non-catechol-type flavonoids could be important for their inhibitory potencies and mechanisms against Aβ42 aggregation.